2021
DOI: 10.1007/s00276-021-02712-x
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical investigation of the proximal vertebral arteries (V1, V2) in a select South African population

Abstract: Introduction The most common type of vascular complication during cervical spine surgery is the vertebral artery (VA) injury. The presence of anatomical variation in the artery's morphology has been a significant factor for arterial injury during surgery. Therefore, physicians planning interventions in the craniospinal region need to be aware of the extents of variations. In addition to vascular injury, anatomical variations can predispose to some pathologies in the posterior circulation territor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…V1 tortuosity is not uncommon. Previous studies have found that about 33.3%–39.05% of vertebral arteries have V1 tortuosity 11,24,25 . In our included studies, Zhou et al 11 and Su et al 16 provided data on V1 tortuosity, but only the former described the definition of V1 tortuosity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…V1 tortuosity is not uncommon. Previous studies have found that about 33.3%–39.05% of vertebral arteries have V1 tortuosity 11,24,25 . In our included studies, Zhou et al 11 and Su et al 16 provided data on V1 tortuosity, but only the former described the definition of V1 tortuosity.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have found that about 33.3%-39.05% of vertebral arteries have V1 tortuosity. 11,24,25 In our included studies, Zhou et al 11 and Su et al 16 provided data on V1 tortuosity, but only the former described the definition of V1 tortuosity. Chen et al 14 also found that V1 tortuosity was significantly more in the ISR group, but only the p-value was given.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, population groups were distinguished in accordance with “modern systems of racial classification”, which states that South Africa has four main population groups, viz. South African Black (origin in any of the native or African groups); South African Coloured, South African Indian (individuals of Asian descent) and South African White (individuals of European) descent [ 37 , 38 ]. The criteria used in the aforementioned racial classification scheme is skin colour and ancestry [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…South African Black (origin in any of the native or African groups); South African Coloured, South African Indian (individuals of Asian descent) and South African White (individuals of European) descent [ 37 , 38 ]. The criteria used in the aforementioned racial classification scheme is skin colour and ancestry [ 38 ]. This age range was selected as the dentition undergoes various stages of development during this period, and in accordance with South African Census 2011, approximately 44% of South Africans is younger than 20 years [ 4 , 5 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The anatomical variation in the vertebral artery and inadequate information about its variation can cause increased risk of vertebral artery injury during cervical spine surgery [7,8]. Hence this study aims to describe the morphometric variation of the V2 segment of vertebral artery to prevent iatrogenic vertebral artery injury.…”
Section: Introductionmentioning
confidence: 99%